O31 Effectiveness of balance training and strength training protocols to improve functional clinical and patient-reported outcomes. (17th September 2017) - Hall, EA; Chomistek, AK; Kingma, JJ; Docherty, CL
Abstract : Study Design: Randomised Controlled Trial. Objectives: Determine the effect of balance and strength training protocols on improving deficits in patients with chronic ankle instability (CAI). Background: Functional deficits arise following a lateral ankle sprain and individuals with CAI can experience long-term disability. Healthcare practitioners should use functional rehabilitation to improve these deficits. Methods and Measures: Thirty-nine participants with CAI volunteered for this study. Identification of Functional Ankle Instability Questionnaire(IdFAI) determined CAI status. Participants were randomly assigned to: Balance Training Protocol(BTP), Strength Training Protocol(STP), and Control Group(CON). The BTP group completed hop-to-stabilisation balance training, the STP group completed resistance band and PNF strength protocol, and the CON group completed a bike workout. Participants completed training 3x/week for six weeks. Clinical outcome (Balance Error Scoring System(BESS), Star Excursion Balance Test(SEBT), and Side Hop Test(SHT)) and patient-reported outcome measures (Foot and Ankle Ability Measure Sport(FAAM-Sport) and Disablement of Physical Activity(DPA)) were evaluated prior to and following the 6 week training. Two multivariate repeated measures ANOVAs were conducted with follow-up univariate analyses. Results: The MANOVA yielded a significant time by group interaction for the clinical measures(p<0.01). Specifically, BTP and STP groups significantly improved from pre-test to posttest in each the BESS(BTP: mean difference=4.7, 95%CI=2.8–6.5 and STP: mean difference=3.3, 95%CI=1.5–5.2), SEBT(BTP: mean difference=4.98, 95%CI=2.9–7.04; STP: mean difference=4.1, 95%CI=2.04–6.2), and SHT(BTP: mean difference=1.8, 95%CI=0.8–2.7; STP: mean difference=2.4, 95%CI=1.5–3.4). The CON group did not significantly improve from pre to posttest (p>0.05) in any clinical outcome measure. No significant time-by-group interactions were identified when evaluating the MANOVA of the patient-reported outcomes(p=0.52). However, there was a significant main effect for time (p=0.001). Follow-up analyses revealed significant differences between the pre-test to posttest for the DPAS(p=0.02) and FAAM-Sport(p=0.001). Conclusion: Both training protocols significantly improved balance and functional performance, but all groups improved patient-reported outcomes.